CUSTOMER PARTICIPATION AND QUALITY OF SERVICE IN IMPROVING LOYALTY VISITORS IN TOURISM PARK - UBUD, SAHNAZ (Universitas Brawijaya, Indonesia, 2017)
Agrotourism is one of the government's commitment to further improve the quality of tourism in the region and the agrotourism customers play an important role in the agrotourism destination, in this case, is Mekarsari Fruit Garden in improving loyalty. The purpose of this research is to know the role of customer participation and the quality of service in improving loyalty at Fruit Park Mekarsari, West Java. Respondents from this study were visitors who took part in the Mekarsari Garden Tour Package. Questionnaires were given directly after the respondents participated in following the green land package. The number of samples in this study was 144 respondents. Model and Data Analysis Technique for this research used PLS (Partial Least Square). The results of this study indicate that there is no direct correlation between motivation and loyalty, but there is a significant relationship between motivation and loyalty if we consider Service Quality to improve customer loyalty. This indicates that customer motivation will play an important role in improving customer loyalty if customers also feel the quality of service well.